2017
DOI: 10.1186/s12887-017-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

Premature atherosclerosis in children with beta-thalassemia major: New diagnostic marker

Abstract: BackgroundEarly vascular alteration, atherosclerosis and coronary artery disease have emerged as important cardiovascular complications among beta-thalassemia major (B-TM) patients. The aims of the current study were to assess the prevalence of premature atherosclerosis among our B-TM patients, and to investigate the diagnostic value of serum Osteoprotegerin assay as an early biomarker for atherosclerosis.MethodsThis cross-sectional study was conducted at Hematology unit - Pediatric Department, Zagazig Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
33
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 46 publications
(54 reference statements)
13
33
0
6
Order By: Relevance
“…Prenner and Chirinos, 7 Zapolski et al, 8 and Sahin et al 9 found an increase of arterial stiffness parameters in diabetes mellitus, end stage renal and thalassemia major (TM) diseases compared with healthy in the order given. In addition, considering TM patients, Sherief et al 10 used the method of carotid artery intima media thickness and found a significant increase, while Cusmà Piccione et al 11 did not find. But the arterial stiffness was increased significantly.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prenner and Chirinos, 7 Zapolski et al, 8 and Sahin et al 9 found an increase of arterial stiffness parameters in diabetes mellitus, end stage renal and thalassemia major (TM) diseases compared with healthy in the order given. In addition, considering TM patients, Sherief et al 10 used the method of carotid artery intima media thickness and found a significant increase, while Cusmà Piccione et al 11 did not find. But the arterial stiffness was increased significantly.…”
Section: Introductionmentioning
confidence: 98%
“…2 Many studies have been conducted about the aortic elastic changes due to various diseases. [4][5][6][7][8][9][10][11] Bayar et al 4 found changes in arterial stiffness parameters in patients with celiac diseases compared with the healthy when Ülger et al 5 did not find any changes in asthma patients. In this regard, Bektaş et al 6 found a significant change in asthmatic patients compared with posttreatment asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…β‐Thalassaemia major (β‐TM), a hereditary haemolytic anaemia induced by a dysfunction of β‐chains synthesis in haemoglobin, results from a β‐globin genetic mutation . It is prevalent in people of Mediterranean, central African, Southeast Asian, and South American descent.…”
Section: Introductionmentioning
confidence: 99%
“…3 Kadar zat besi yang tinggi di dalam darah akan menyebabkan peningkatan risiko terjadinya atherosklerosis melalui peningkatan zat radikal bebas. 4 Selain itu, anak dengan thalassemia beta juga memiliki risiko atherosklerosis prematur sebagai akibat dislipidemia. 3 Beberapa penelitian telah menunjukkan bahwa akumulasi zat besi di tubuh dapat menimbulkan gangguan profil lipid.…”
unclassified
“…8 Dislipidemia pada thalassemia mayor disebabkan oleh berbagai faktor, antara lain dilusi plasma akibat anemia, meningkatnya aktivitas eritropoeisis yang disertai dengan pengambilan kolesterol oleh makrofag dan histiosit dalam sistem retikuloendotelial, gangguan fungsi hati karena penimbunan zat besi, gangguan hormonal, dan menurunnya aktivitas lipolisis di luar hati. 4 Gambaran profil lipid pada thalassemia memiliki korelasi dengan penumpukan zat besi di dalam darah. Penumpukan zat besi di dalam hati akan menimbulkan kerusakan hepatosit dan sel retikuloendotelial, yang ditandai oleh perkembangan fibrosis hingga terjadi sirosis.…”
unclassified